The Nature of Religion: Divine and Human - Lozuraitis, Albinas (Problemos, 1983)
The development of religion and its modern philosophical and sociological interpretations constantly give rise to the old question of the nature of religion and its Marxist interpretation. The definition of religion on the basis of the illusion of supernatural reality does not exceed the boundaries of phenomenological description of religious experience. The atheistic denial of reality of the supernatural world is at the same time the denial of religion and thus the problem of its definition becomes non-existent. The pre-Marxist atheism tries to solve the unsolvable problem, i.e., to present a gnoseological explanation of the existence of false ideas. K. Marx, having overcome the gnoseological view, finds a method of explaining the necessity and universality of the erroneous views: he reduces them to the material basis – to the estranged character of social relations, and this helps to reveal the essence of ideological illusion in general, and religious illusions taken separately. From the point of view of Marxist atheism which recognizes the practical causes of the alienation in human relations, the criticism of religious estrangement is not considered a mainly theoretical task.